Overexpression of Umellularia californica FatB thioesterase affects plant growth and lipid metabolome leading to improved drought tolerance in Arabidopsis and tomato - Wang, Shuangshuang; Yang, Biyun; Liang, Yitao; Zou, Xinrui; Xu, Min; Zhao, Chan; Wang, Yiwen; Ni, Bing; Zhu, Pinkuan; Jiang, Yina (Frontiers in Plant Science, 2025)
Frequent and extreme drought exerts profound effects on vegetation growth and production worldwide. It is imperative to identify key genes that regulate plant drought resistance and to investigate their underlying mechanisms of action. Long-chain fatty acids and their derivatives have been demonstrated to participate in various stages of plant growth and stress resistance; however, the effects of medium-chain fatty acids on related functions have not been thoroughly studied. Here, we integrate lipidomic, transcriptomic, and genetic analyses to elucidate the roles of the medium-chain acyl-acyl carrier protein thioesterase of Umellularia californica FatB (UcFatB) in drought tolerance and plant growth. Arabidopsis and tomato transgenic lines overexpressing UcFatB showed that the medium chain fatty acids mainly affect the male reproductive process of plant development. Transcriptomic and non-targeted lipid metabolomic combination analysis revealed significant changes in lauric acid-related metabolic pathways, as evidenced by increased phosphatidylcholine accumulation and upregulated stress-response gene expression. Consistent with the thicker waxy cutin layer and increased membrane integrity, UcFatB-overexpression enhanced drought tolerance in both Arabidopsis and tomato. Furthermore, methyl laurate and phosphatidylcholine application improved tomato drought resistance and fruit yield. These findings provide new insights into the potential genetic resources and cost-effective chemicals for enhancing drought resistance in crops.